Research and Practice on Innovative Integrated Education in the Acupuncture and Tuina Discipline from the Perspective of Curriculum-Based Ideological and Political Education - Gang, Xiaochao; Liang, Zhongyi; Liu, Mingjun; Zhang, Xin; Zhong, Chongwen; Li, Huijing (Asian agricultural research, 2025)
The educational philosophies of curriculum-based ideological and political education and professional innovation-inteerated education, both serving as guiding ideologies aligned with contemporary educational development, have been persistently deepened in the pedagogical practices of higher education institutions in recent years, significantly propelling the advancement of China's higher education. However, research remains scarce regarding how these two approaches can mutually complement each other to jointly advance the education of the Acupuncture and Tuina Discipline. Conseauently, this study explores pathways for innovation-integrated education in the Acupuncture and Tuina Discipline from the perspective of curriculum-based ideological and political education. Through educational research and practical implementation, it aims to provide innovative ideas and methods for enhancing the quality of talent cultivation in the Acupuncture and Tuina Discipline.